Recovery after total intravenous general anaesthesia or spinal anaesthesia for total knee arthroplasty: a randomized trial - Harsten, A; Kehlet, H; Toksvig-Larsen, S (British journal of anaesthesia : BJA, 2013)
This study was undertaken to compare the effects of general anaesthesia (GA) and spinal anaesthesia (SA) on the need for postoperative hospitalization and early postoperative comfort in patients undergoing fast-track total knee arthroplasty (TKA). One hundred and twenty subjects were randomly allocated to receive either intrathecal bupivacaine (SA group) or GA with target controlled infusion of propofol and remifentanil (GA group). Primary outcome was length of hospital stay (LOS) defined as time from end of surgery until the subject met the hospital discharge criteria. Secondary outcome parameters included actual time of discharge, postoperative pain, intraoperative blood loss, length of stay in the Post Anaesthesia Care Unit, dizziness, postoperative nausea and vomiting, need for urinary catheterization and subject satisfaction. GA resulted in shorter LOS (46 vs 52 h, P<0.001), and less nausea and vomiting (4 vs 15, P<0.05) and dizziness (VAS 0 mm vs 20 mm, P<0.05) compared with SA. During the first 2 postoperative hours, GA patients had higher pain scores (P<0.001), but after 6 h the SA group had significantly higher pain scores (P<0.001). Subjects in the GA group used fewer patient-controlled analgesia doses and less morphine (P<0.01), and were able to walk earlier compared with the SA group (P<0.001). Subjects receiving SA would request a change in the method of anaesthesia in the event of a subsequent operation more often than the GA subjects (P<0.05). GA had more favourable recovery effects after TKA compared with SA.